Unveiling the Dual Impact of Competence and Discipline on Performance in Indonesia: Mengungkap Dampak Ganda Kompetensi dan Disiplin terhadap Kinerja di Indonesia - Syauqi, Ahmad; Awan, Edi; Mubarok, Imam Anas; Zulkarnain, Rahmat (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the impact of employee competence and discipline on performance in a company in Pamekasan Regency. Although previous research has linked competencies to performance, the specific interaction between discipline and competencies and their combined effect on performance is less explored. This study aims to fill this knowledge gap by assessing how competence directly affects performance and how it affects employee discipline which in turn affects performance. Using structural equation modeling on data from 39 respondents, findings show that competence significantly improves performance directly, and also indirectly through improved discipline. However, the direct effect of competence on performance is stronger than its indirect effect through discipline. These insights emphasize the importance of integrating a competency-based approach with a disciplined work environment to optimize employee performance. This study contributes to the competency-based performance literature and offers practical implications for improving employee productivity through competencies and targeted discipline. Highlights: Direct Impact of Competence: Competence significantly enhances employee performance directly, highlighting its pivotal role in productivity. Role of Discipline: Discipline not only supports but also mediates the relationship between competence and performance, indicating its crucial function in organizational success. Comparative Influence: The direct influence of competence on performance is more pronounced than its indirect effect through discipline, suggesting primary focus on competence development for immediate performance gains. Keywords: Competence, Discipline, Employee Performance, Structural Equation Modeling